A Critical Review of Epistemological and Methodological Issues in Cross-Cultural Research - Yeganeh, Hamid; Su, Zhan; Chrysostome, Elie (Journal of Comparative International Management)

(untitled) (Management Futures, 2004)
Abstract Cross-cultural management research suffers from many shortcomings. While some of these shortcomings are related to methodology, others can be identified as epistemological problems. By recognizing that epistemological positions determine methodological approaches, this paper attempts to discuss both epistemological and methodological issues in cross-cultural research. Based on extant literature, major drawbacks are discussed and some suggestions for future research are presented.